Early Reading: An Analysis of Beginning Reading Difficulties in First-Grade Students - Khairunnisa, Mutia; Sa'odah; Huliatunisa, Yayah (Jurnal Elementaria Edukasia, 2025)
Early reading ability is a crucial stage in primary education as it lays the foundation for students’ literacy development at the next levels. However, many first-grade students struggle with letter recognition, distinguishing similarly shaped letters, spelling words correctly, and understanding texts. This study aims to identify early reading difficulties among first-grade students at SDN Keranggan, South Tangerang. The research employs a qualitative descriptive method using observation, interviews, and document analysis as data collection techniques. The findings indicate that several students face obstacles in recognizing letters, spelling words accurately, and comprehending reading materials. These difficulties arise due to a lack of practice at home and low learning motivation. Furthermore, students exhibit challenges in distinguishing visually similar letters, such as "b" and "d" or "p" and "q," which leads to errors in reading accuracy. To address these issues, teachers implement various strategies, including visual media, multisensory approaches, and picture-based reading exercises, which have shown a positive impact on students' reading proficiency. Additionally, parental involvement plays a crucial role in supporting children’s reading development, with activities such as reading together, using interactive learning tools, and fostering a reading-friendly environment. With adequate support from both the school and home environments, early reading difficulties can be minimized, allowing students to develop effectively and comprehend texts proficiently.